The entangled pandemic: Deep incarnation in creation - Simmons, Ernest L. (Dialog, 2021)
The metaphorical appropriation of quantum entanglement (non-local relational holism) helps to conceptualize the physical relationship of God to creation in a way that can support the understanding of deep incarnation. The relational holism of Divine entanglement helps clarify how deep incarnation is possible. The pandemic is then approached as an example of evolutionary theodicy that can be addressed through such entangled deep incarnation. This in turn provides the basis for deep resurrection, which, while acknowledging suffering and death in the natural world, also affirms hope and life in Christ.